Blue laser diodes for trace matter detection - Holc, Katarzyna; Bielecki, Zbigniew; Wojtas, Jacek; Perlin, Piotr; Goss, Jakub; Czyżewski, Adam; Magryta, Paweł; Stacewicz, Tadeusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We present spectroscopic applications of GaN-based laser diodes (LDs), fabricated and developed at the Institute of High Pressure Physics and its spin-off company TopGaN. LDs were manufactured using MOCVD technology. For spectroscopic applications we applied pulsed operated lasers generating the radiation in 395–430 nm spectral range reaching the power of 200 mW within the light pulses of 30–150 ns at the repetition rates of 10 kHz. These LDs were successfully applied to the detection of nitrogen dioxide in free atmosphere using cavity ring down spectroscopy (CRDS) sensor. Cw operated lasers generating within the spectral range of 385–420 nm and reaching powers up to 300 mW were adapted for atomic spectroscopy. Using external cavity tuning with diffraction grating in Littrow configuration, we obtained the stability of single mode generation better than 100 MHz within the periods of 30 minutes without any additional frequency stabilization feedback.
Optica Applicata, Vol. 40, 2010, nr 3, s. 641-651
Keywords: optyka; trace matter detection; cavity ring down spectroscopy (CRDS); GaN laser diodes